Three dimensional asset documentation using terrestrial laser scanner technology - Ashim, Ahmad Bazil (Faculty of Geoinformation and Real Estate, Universiti Teknologi Malaysia, 2011)
Asset documentation is a detailed record or inventory of the properties located within a room or a building. It is important to record the assets in case of property loss happen inside the premise especially when that premise caught fire, earthquake, robbery and others. The instrument used in this study is Faro Laser Scanner Photon 120/20. The object of the study is the computer room of Photogrammetry Lab, Faculty of Geoinformation and Real Estate. The final output of this study is the 3D model of the assets available inside the building. Before 3D model can be formed, the scanned data which is in the form of point cloud generated from the laser scanner have to be registered and georeferenced in order to combine the scans. The combine scans is the representation of the whole area of work surveyed from every scan points. These processes use Faro Scene, software that comes together with the laser scanner. By introducing this method, large scale asset documentation such as for factories and schools would be very beneficial rather than conventional method. The next process is to model the point cloud using AutoCAD 2011. Every item available on the room such as desks, chairs, cubicles, computers, whiteboard, projectors and cupboard are modeled and each of these items was inserted with attributes so that we can know the information of each items